Stage 0 Charcot Neuroarthropathy in the Diabetic Foot: An Emerging Narrow Window of Opportunity?. (December 2022) - Ahluwalia, Raju; Armstrong, David G.; Petrova, Nina; Papanas, Nikoloas; Edmonds, Michael
In a world where popular culture and concepts can become the norm without all the rigors of normal scrutiny, our attention is focused on identifying Charcot neuroarthropathy (CN) at a stage before radiological bone destruction occurs. The rationale is that early recognition can prevent a destructive chain of events and thus potentially reduce the burden to patients and health care providers. In this article, we describe the evolution of stage 0 CN, and the use of modern imaging in characterizing the abnormalities recognized by these modalities and how they aid our understanding and supplement our knowledge. We review the potential of these imaging modalities, assessing how far we have come in characterizing stage 0 and if we have robust criteria for the identification of stage 0 in the natural history of CN.